Analysis of fluoxetine and norfluoxetine in human plasma by HPLC-UV using a high purity C18 silica-based SPE sorbent - Nazario, Carlos Eduardo Domingues; Lima Gomes, Paulo Clairmont Feitosa de [UNESP]; Lancas, Fernando Mauro (Royal Society of Chemistry (RSC), 2014)
This paper reports on the development and validation of a simple and sensitive method that uses solid phase extraction (SPE) and liquid chromatography with ultraviolet detection to analyze fluoxetine (FLX) and norfluoxetine (NFLX) in human plasma samples. A lab-made C18 SPE phase was synthesized by using a sol–gel process employing a low-cost silica precursor. This sorbent was fully characterized by nuclear magnetic resonance (NMR), Fourier-transform infrared spectroscopy (FT-IR), and scanning electron microscopy (SEM) to check the particles' shape, size and C18 functionalization. The lab-made C18 silica was used in the sample preparation step of human plasma by the SPE-HPLC-UV method. The method was validated in the 15 to 500 ng mL 1 range for both FLX and NFLX using a matrix matched curve. Detection limits of 4.3 and 4.2 ng mL 1 were obtained for FLX and NFLX, respectively. The repeatability and intermediary precision achieved varied from 7.6 to 15.0% and the accuracy ranged from 14.9 to 9.1%. The synthesized C18 sorbent was compared to commercial C18 sorbents. The average recoveries were similar (85–105%), however the lab-made C18 silica showed fewer interfering peaks in the chromatogram. After development and validation, the method using the lab-made C18 SPE was applied to plasma samples of patients under FLX treatment (n ¼ 6). The concentrations of FLX and NFLX found in the samples varied from 46.8–215.5 and 48.0–189.9 ng mL 1 , respectively.